Household Expenditure and the Income Tax Rebates of 2001 - David S. Johnson; Jonathan A. Parker; Nicholas S. Souleles (Princeton University, Woodrow Wilson School of Public and International Affairs, 2004)
Under the Economic Growth and Tax Relief Reconciliation Act of 2001, most U.S. taxpayers received a tax rebate between July and September, 2001. The week in which the rebate was mailed was based on the second-to-last digit of the taxpayer's Social Security number, a digit that is effectively randomly assigned. Using special questions about the rebates added to the Consumer Expenditure Survey, we exploit this historically unique experiment to measure the change in consumption expenditures caused by receipt of the rebate and to test the Permanent Income Hypothesis and related models. We find that households spent about 20-40 percent of their rebates on non-durable goods during the three-month period in which their rebates were received, and roughly another third of their rebates during the subsequent three-month period. The implied effects on aggregate consumption demand are significant. The estimated responses are largest for households with relatively low liquid wealth and low income, consistent with liquidity constraints.
Keywords: E21; H31; E62; 330; consumption; saving; Life-Cycle model; Permanent-Income Hypothesis; liquidity constraints; fiscal policy; tax cuts; tax rebates; windfalls; Einkommensteuer; Steuerbegünstigung; Verbraucherausgaben; USA